2018
DOI: 10.1152/jn.00245.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum and cognition in multiple sclerosis

Abstract: Kalron et al. report people with Multiple Sclerosis (PwMS) who fall show a decreased cerebellar volume along with decreased overall cognition compared to non-fallers. While this paper focuses on cerebellar and cognitive alterations in PwMS, these findings may also be explained by additional factors such as aging and have the potential for broader impact in additional clinical populations who simultaneously experience cognitive and mobility dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…38 Most of the MRI abnormalities that were reported to have an impact on cognition were either volumetric changes in gray or white matter or functional MRI abnormalities such as total cerebellar volume, cerebellar gray matter volume, cerebellar gray matter volume, hubs and network properties, fractional anisotropy, and voxelbased morphometry abnormalities. [39][40][41][42][43] Data about the impact of total lesion load in cerebellum and cerebellar peduncles on cognition were conflicting. Some authors such as Valentino and colleagues, 37 found no significant correlation between total lesion load in the cerebellum and cognition in a cohort of RRMS patients, whilst Cerasa and colleagues, 44,45 reported the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…38 Most of the MRI abnormalities that were reported to have an impact on cognition were either volumetric changes in gray or white matter or functional MRI abnormalities such as total cerebellar volume, cerebellar gray matter volume, cerebellar gray matter volume, hubs and network properties, fractional anisotropy, and voxelbased morphometry abnormalities. [39][40][41][42][43] Data about the impact of total lesion load in cerebellum and cerebellar peduncles on cognition were conflicting. Some authors such as Valentino and colleagues, 37 found no significant correlation between total lesion load in the cerebellum and cognition in a cohort of RRMS patients, whilst Cerasa and colleagues, 44,45 reported the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Lower cerebral glucose metabolism levels in the FrA and hippocampus related to memory deficits have also been found in our previous PET study ( Park et al, 2013 ; Lim et al, 2016 ; Ye et al, 2016 ). Furthermore, other groups have reported cognitive decline-associated decreases in cerebral glucose metabolism in the Cb ( Schreck et al, 2018 ; Liang and Carlson, 2019 ; Nishida et al, 2019 ). In the current study, the decrease in the cerebral glucose metabolism in the FrA persisted at the 7-month time-point.…”
Section: Discussionmentioning
confidence: 94%
“…In their review on balance improvement, Gunn et al reported a positive influence of exercise interventions on balance in pwMS [113]. Other studies focusing on general motor rehabilitation in pwMS pointed at the issue that motor learning consists of three stages (cognitive, associative and autonomous phase), where the first stage depends on the person's cognitive abilities [114], and the fact that cognitive impairment is very common in pwMS thus connects cognitive and mobility dysfunction [115].…”
Section: Coordination/balancementioning
confidence: 99%